Applications of Particle Swarm Optimization Algorithm to Solving the Economic Load Dispatch of Units in Power Systems with Valve-Point Effects - Hossein Shahinzadeh; Sayed Mohsen Nasr-Azadani; Nazereh Jannesari (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Reduction of operating costs in power system in order to return the investment costs and more profitability has vital importance in power industry. Economic Load Dispatch (ELD) is one of the most important issues in reducing operating costs. ELD is formulated as a nonlinear optimization problem with continuous variables within the power plants. The main purpose of this problem is optimal planning of power generation in power plants with minimum cost by total units, regarded to equality and inequality constraints including load demand and the range of units' power productivity. In this article, Economic Load Dispatch problem has been modeled by considering the valve-point loading effects with power plants' constraints such as: the balance of production and consumption in system, the forbidden zones, range of production, increasing and decreasing rates, reliability constraints and network security. To solve the problem, Particle Swarm Optimization (PSO) Algorithms has been employed. To evaluate the effectiveness of the proposed method, the problem has been implemented on a power system with 15 generating units and the results have been evaluated.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6720